Determinan Penggunaan Digital Banking Pada Generasi Milenial Muslim: Pendekatan Technology f Acceptance Model (Studi Kasus Di Kota Jayapura, Indonesia) - Ira Eka Pratiwi; Fachrudin Fiqri Affandy; Yuyun Rosalina (ITB AAS INDONESIA Surakarta, 2020)
Digital banking is a technology application developed to make customer transactions easier. Nowadays, millennials have become the market targetting of the banking sector, especially for using digital banking, since they prefer to something modern and instant. This research purposed to examine the determinants of Muslim millennial customer in adopting digital banking with the implementation of the model of technology acceptance (TAM) which includes two predictors including the perceived ease of use and perceived of usefulness. The method was a quantitative method using primary data collected by using questionnaires to 100 Muslim millennials as respondents in Jayapura City, the eastern region in Indonesia. Data collected analyzed wiith multiple liniear regressions. The results showed that both the independent variables, i.e the perceived ease of use and perceived of usefulness significantly affect the intention of Muslim millennials customers in using digital banking partially and simultaneously.